A critical discussion of modelling, performance assessment, and design recommendations-based case study of solar dish Stirling system - Alkhalaf, Qusai; Kumar, Raj; Suri, Amar Raj Singh; Thapa, Sashank; Lee, Daeho; Alwetaishi, Mamdooh; Agbulut, Uemit (SPRINGER, 2025)
Solar dish Stirling system (SDSS) has generated power in rural, urban, and isolated places. Its performance is affected by weather, irradiance, wind speed, dish diameter, receiver diameter, and type of Stirling engine (SE). The modelling and design changes enhance the SDSS performance. This study covers SDSS performance optimization, design recommendations, and case analysis. The study encompasses a review of investigations of SDSS in several nations and SDSS facilities with wide examination in several domains such as solar power plants, hybridization and storage, micro-co-generation, water desalination, and solar cookery. This paper provides detailed information on SDSS performance improvement modelling and design adjustments. Reviewing the modelling and design modification studies, important findings are presented, and optimum design parameter values at specific sites are offered. The range of output power in the reviewed literature varies from 0.103 kW to 58 kW, and the overall efficiency of the system (eta System) is between 10.41% and 25%. The current work has the study of SDSS modelling applied to a case study in Solan City (India), based upon which optimum design recommendations and direction of future research are suggested. The study estimates SDSS's maximum efficiency and output power as 26.17% and 40.43 kW, respectively.
Keywords: Solar energy; Solar dish Stirling system; Parabolic dish reflector; Stirling engine; THERMODYNAMIC MODEL; CAVITY RECEIVER; PARABOLIC DISH; NATURAL-CONVECTION; ENGINE SYSTEM; COMBINED HEAT; POWER; OPTIMIZATION; CONSTRUCTION; SIMULATION; Thermodynamics; Chemistry